2004
DOI: 10.1111/j.1444-0903.2004.00517.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of serology in determining recent acute Campylobacter infection

Abstract: The use of Campylobacter-specific antibody levels as the sole marker of prior infection is an unreliable method of determining the association between Campylobacter infection and neurological disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Antibody decay, although highly variable between individuals, was demonstrated in longitudinal studies (Strid et al 2001;Cawthraw et al 2002;Taylor et al 2004). Hence, even though anti-Campylobacter IgG antibodies may persist for several years, their high prevalence indicates repeated (symptomless) infection by Campylobacter during life.…”
Section: Serosurveillancementioning
confidence: 99%
“…Antibody decay, although highly variable between individuals, was demonstrated in longitudinal studies (Strid et al 2001;Cawthraw et al 2002;Taylor et al 2004). Hence, even though anti-Campylobacter IgG antibodies may persist for several years, their high prevalence indicates repeated (symptomless) infection by Campylobacter during life.…”
Section: Serosurveillancementioning
confidence: 99%
“…For comparison, figures for acute C. jejuni enteritis patients from a 2004 report by Taylor et al are also shown. 19 The neuropathy group included nine patients with CIDP and five with MMN.…”
Section: Resultsmentioning
confidence: 99%
“…The findings for the two control groups recruited for our prior Campylobacter antibody study were utilized again in the present study. 19 These control groups comprised 420 healthy blood donors with no recent history of Campylobacter infection, and 34 patients with neurological diseases other than MND, CIDP, MMN and GBS, including Parkinson's disease, multiple sclerosis, headache, progressive supranuclear palsy and epilepsy. Data from the control groups were collected concurrently with those from the patient groups.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations